WORKSHOP PERSIAPAN MENGHADAPI DUNIA KERJA DAN TEKNIK INTERVIEW BAGI SISWA KELAS XII SMKS BUDI ASIH TEBET JAKARTA SELATAN - Karya Bakti Kaban; Mira Firlana (ASIAN PUBLISHER, 2023)
Vocational High School is a school that educates its students to be ready to enter the world of work. They are equipped with various knowledge and skills that can be used in the world of work.Class XII is the period when SMK students must stop playing around and take the time to study in order to pass school and state exams. After that focus on finding work. Entering the world of work is not as easy as turning the palm of the hand. Newly graduated SMK students have to take job entrance exams, and compete with people with higher education. Of course, vocational school graduates are starting to wonder to themselves,